CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI SALAH SATU BENTUK MANIFESTASI TATA KELOLA: STUDI KASUS PADA PROGRAM BIRO KEMITRAAN PT. SEMEN GRESIK (PERSERO) TBK - Finna Farsyani Setiono; Fidelis Arastyo Andono (Jurnal Akuntansi Bisnis, 2017)
This research aims to answer the question of how the corporate social responsibilities practice, in term of “bina mitra” program could be one of the corporate governance manifestations in the case of PT Semen Gresik (Persero), Tbk. The responses from the participants nearby the corporation would also be carefully examined qualitatively to get the picture of how the CSR had been practiced. This research was conducted as a qualitative research with case study method with the object of “bina mitra” program, PT Semen Gresik (Persero) Tbk.  The first research finding is that the company runs the CSR and implements the GCG principles along with its environment development. Secondly, GCG principles were carried out very well during the CSR process that makes the CSR one of the corporate GCG manifestations in PT Semen Gresik (Persero), Tbk.  Keywords: corporate governance, corporate social responsibility, manifestation